EFFETS DE LA LIBERATION MYOFASCIALE SUR LES IJOSSIARDS DES JOUEURS DE HANDBALL (Fiep Bulletin - online, 2024)
Introduction: Handball is a collective sport modality that requires sporting gestures of high physical demand. The goalkeeper is a primordial position in the team, since he is the last defensive player. These athletes are trained to overcome the physical, technical and psychological demands of the sport, subjecting themselves to factors that go beyond their anatomical and physiological limits, resulting in a predisposition to injuries. Methods: The methodology will include a detailed evaluation of the athlete before and after the application of the technique, an evaluation form will be used in addition to the use of a fleximeter to evaluate the ROM and the Bank of Weels to measure flexibility. This research aims to analyze the effects of the myofascial release technique and its repercussions on the range of motion of hamstrings in goalkeepers in a youth female amateur handball team in the city of São Miguel do Iguaçu-PR.
Keywords: Physiotherapy; Performance; Sport; Health